1998
DOI: 10.1159/000023997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structure Modifications on IgE Binding Properties of Serum Albumins

Abstract: Background: Bovine serum albumin (BSA) is one of the most widely studied proteins; its structure is well–known and its antigenic characteristics have been described in studies performed in in vitro and animal models. The aim of our work was to evaluate the role of BSA conformation in its antigenicity (recognition by circulating IgEs from allergic children). Methods: This study was performed using electrophoresis associated with the immunoblotting technique, where sera from children sensitized to BSA (as shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
2
20
1
2
Order By: Relevance
“…In contrast, previous studies by our group showed that serum albumin antigenicity is only partially correlated with its native three-dimensional structure [8]. …”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In contrast, previous studies by our group showed that serum albumin antigenicity is only partially correlated with its native three-dimensional structure [8]. …”
Section: Introductioncontrasting
confidence: 59%
“…After polyacrylamide gel electrophoresis (PAGE), immunoblotting was performed as described by Restani et al [8]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that allergy to meat is rare; positive skin prick tests to beef were described in only 7.69 % of children with atopic dermatitis [3,4]. However, BSA has been identified as one of the most important allergens in bovine meat, with a high degree of crossreactions due to the significant sequence and structural similarities of serum albumin from different organisms [5,6]. In recent years, ultrahigh pressure (UHP) has been more frequently applied instead of traditional thermal treatment, especially for pasteurization [7].…”
Section: Introductionmentioning
confidence: 99%